(untitled) (Al-Mukhtar Journal of Economic Sciences, 2021)
This study aims to identify the visions and positions of major countries and regional international organizations, on top of that, the Security Council and the General Assembly, where many international initiatives and proposals were monitored that demanded the application of democracy within the Security Council in terms of voting, the veto, and continental representation within the Council, in addition to the demand for these initiatives to grant the General Assembly the right to monitor the performance of the Security Council, especially with regard to international issues that threaten international peace and security. Although some of the reform and development initiatives originated from some major countries, the approval of these initiatives met with public and sometimes tacit rejection by the permanent members of the Security Council. A real positive change and development with regard to the voting systems and membership within the Security Council or the General Assembly; This is because these countries are convinced of the negative effects this reform will have on their own interests and global influence. The study reached several conclusions, including: The voting and decision-making system within the Security Council made the interference of major countries in the internal affairs of other countries a justification for that intervention in matters that are at the core of their competence, and that is the slogan of "human protection and internal security, and that is in the name of human rights or national security." Under the umbrella of international legitimacy.